Biochemical, Hematological and Immunological Indices Among MDR-TB on Second Line Anti TB and MDR-TB-HIV Co-Infected Patients on Second Line Anti TB and ARV Drugs for a Six -Month Treatment (Tanzania Medical Journal, 2020)
BackgroundTuberculosis (TB) is a major global health problem, and anti-tuberculosis drugs can impose a hazardous effect on the patient’s liver, leading to hepatotoxicity, and are a major problem in tuberculosis patients. This study aimed to determine hematological, biochemical and Immunological indices in patients with Multi Drug Resistant Tuberculosis TB (MDR-TB) with or without HIV infection, undergoing treatment with second-line Anti TB plus ARV’s or second-line anti TB.ObjectiveTo assess the hematological, biochemical and immunological indices of patients with or without HIV-MDR-TB at the Kibong’oto Infectious Disease Hospital over a six-month treatment.MethodologyThis was a descriptive study. A total of 198 MDR-TB patients aged between 18 and 50 years or above, were collected from Kibong’oto Infectious Disease Hospital from April 2017 to October 2019 involving patients who were on treatment for MDR-TB and MDR-TB/HIV. Selected hematological, biochemical and immunological indices were determined at the onset of treatment from both groups of patients, and then same parameters determined after six months of treatment with second line anti-TB and second line anti-TB plus ARVS for both groups, respectively. Data were analyzed using paired samples t-test by Stata version 13.ResultsThere was an elevated level of AST and ALT in MDR-TB with HIV infected patients compared to the MDR-TB group. Liver enzyme activities (ALT, AST, and ALP) were increased significantly after six months of treatment in MDR-TB/HIV co-infection compared to MDR-TB (p<0.01). While Hb decreased significantly over the six months in the MDR-TB-HIV co-infected patients, WBC increased significantly during the same group and treatment period (p<0.01).ConclusionOur findings imply that a combination of second-line anti TB with ARVs confers more toxicity to the liver and induce more hematological effects than anti-TB use alone. Our findings underscore the need for close monitoring during MDR-TB especially in co-infection with HIV for optimal management.Keywords: Tuberculosis, MDR-TB, HIV, Hematology, Biochemical.